P 51. Sonographical study on morphological alterations of the peripheral nerves in a cohort of patients with Parkinson's Disease. Issue 8 (August 2021) - Scholz, L.; Huckemann, S.; Müller, K.; Kools, S.; Hilker, L.; Ebner, L.; Kirchgässler, A.; Kühn, E.; Averdunk, P.; Gold, R.; Tönges, L.; Pitarokoili, K.
Abstract : Introduction . The reported prevalence of axonal polyneuropathy (PNP) in patients with Parkinsońs Disease (PD) is about 55%. Alpha synuclein pathology as well as levodopa exposure are discussed as the main driving factors [Doppler et al. 2010; Toth et al. 2010]. The aim of this study was to evaluate morphologic alterations of peripheral nerves in PD- PNP using nerve ultrasound. A recent study of our group showed alterations mostly in entrapment sites [Kühn et al. 2020]. We investigated this observation in a larger cohort. Patients/Methods. Peripheral nerves of 85 patients with PD were evaluated with nerve ultrasound. The cohort had a mean age of 71 years and a mean disease duration of seven years. The cross-sectional-area (CSA) was measured at 14 different anatomical points, of which five were typical entrapment sites (median nerve at carpal tunnel, ulnar nerve at loge de Guyon and cubital tunnel, fibular nerve at the fibular head, tibial nerve at the ankle) and nine non entrapment sites (median nerve at forearm and upper arm, ulnar nerve at forearm and upper arm, radial nerve, vagal nerve, fibular nerve at popliteal fossa, tibial nerve at popliteal fossa and sural nerve). The values were compared with reference values of our group [Kerasnoudis et al. 2013]. Results. Regarding the stated entrapment sites eight patients had an enlarged CSA (cut-off value of 12.57 mm 2 ) of the median nerve at the carpal tunnel. 26 patients of the ulnar nerve at the Guyon loge (cut-off value of 7.22 mm 2 ) and 38 at the cubital tunnel (cut-off value of 8, 13 mm 2 ). The CSA of the fibular nerve at the fibular head was enlarged in 57 patients (cut-off value of 13, 9 mm 2 ). 56 patients showed an enlargement of the CSA of the tibial nerve at the ankle (cut-off value of 9, 26 mm 2 ). A much lower number of nerves with CSA increase were found at the non-entrapment sites. At each site no more than 10 patients had CSA-values larger than the cut off value. Conclusion/Discussion. Our results could demonstrate a non symptomatic nerve damage at sites with a higher mechanical burden in the case of PNP in PD. To what extend enhanced structural vulnerability due to the alpha-synuclein pathology contributes to this finding remains to be examined. Longitudinal examination is necessary to reveal dynamic alterations in different disease stages. Table 1. CSA values at the different measured sites. Fig. 1.